Countering ethnic hatred and its pedagogical approach in social studies: focusing on multiple social identities - Chun, Jabae; Eun, Ji-Yong (Frontiers in Education, 2025)
This study addresses prejudice and discrimination against ethnic minorities and examines their causes and solutions within the social studies classroom. Grounded on Social Identity Theory, this study highlights the significance of teaching students about multiple social identities to reduce bias. To enhance classroom applicability, this study proposes a teaching model for social studies curricula aligned with the inquiry design model (IDM) of the National Council for the Social Studies (NCSS). Also, it presents a pedagogical format for high school instruction, which adheres to the C3 Framework for Social Studies State Standards in the United States and the revised 2022 Social studies curriculum in South Korea. This model will empower students to contribute to building a society where diverse backgrounds are acknowledged and respected.